Estudo do crescimento, eficiência de biofiltração e cinética de absorção de nutrientes (N-NH, N-NO e P-PO4³) da macroalga Gracilaria cervicornis (Turner) J. Agardh - Carneiro, Marcella Araújo do Amaral (2007)
The objective of this study was to examine the growth of Gracilaria cervicornis cultured in a shrimp (Litopenaeus vannamei) pond and to determine the absorption efficiency and the kinetics parameters (Vmax, Ks e Vmax:Ks) of this macroalgae for the nutrients N-NO3-, N-NH4+ and P-PO4-3, aiming at its use as bioremediatory of eutrophicated environments. For this study, two experiments (field and laboratory) were developed. In the field study, the seaweed was examined in relation to the growth and the biomass. In the laboratory experiment, the absorption efficiency of G. cervicornis was measured through the monitoring of the concentration of the three nutrients (N-NO3-, N-NH4+ e P-PO4-3) during 5 hours and the kinetic parameters were determined through the formula of Michaelis-Menten. The results obtained in this study demonstrated that G. cervicornis benefited from the available nutrients in the pond, increasing 52.4% of its biomass value after 30 days of culture. It was evidenced that the variability of the biomass could be explained through the salinity, availability of light (transparency and solid particle in suspension) and concentration of N-NO3- in the environment. In the laboratory experiment, the highest absorption efficiency was found in the treatments with low concentration (5 µmol.L-1), being evidenced a reduction of up to 85,3%, 97,5% and 81,2% of N-NH4+, N-NO3- and P-PO43-, respectively. Regarding the kinetic parameters, G. cervicornis presented better ability in absorbing N-NH4+ in high concentrations (Vmax = 158,5 µmol g-1 dry wt h-1) and P-PO43- in low concentrations (Ks = 5 µmol.L-1 e Vmax:Ks = 10,3). The results of this study show that G. cervicornis could be cultivated in shrimp ponds, presents a good capacity of absorption for the tested nutrients and is a promising candidate for biorremediation in shrimp pond effluent